Pengaruh Jenis Kemasan Terhadap Mutu Wortel (Daucus Carota L.) Selama Penyimpanan Dingin - Sukarame, Cerry; Lengkey, Lady; Longdong, Ireine A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aims to analyze and compare the effectiveness of four types of packaging, namely: vacuum, non-vacuum, plastic wrapping, and perforation in maintaining the quality of carrots (Daucus carota L.) during cold storage until signs of damage appear, based on parameters of changes in weight, water content, color, and texture. The method used is an experiment with four treatments of packaging types on carrots stored in a refrigerator at a temperature of 2°C-4°C for 30 days. Observations were made on changes in weight, color (L*, a*, b*), texture, and moisture content of the carrots in each treatment. The results of the study show that in vacuum packaging, the average weight change was 0.00-0.35 g (23 days), the average moisture content change was 87%-86% (30 days), the average L* color change was 54.83, a* of 33.59, and b* of 54.83, and a texture of 4.73-3.40 N. In non-vacuum packaging, the average weight change was 0.00-0.20 g (17 days), the average moisture content change was 86.33%-86.0% (30 days), the average change in color L* was 56.72, a* was 30.10, and b* was 56.72, and the texture was 4.73-2.93 N. In perforated packaging, the average change in weight was 0.26-8.61 g (30 days), the average change in moisture content was 87%-86% (30 days), the average change in color L* was 55.04, a* was 27.32 and b* was 55.03, and the texture was 4.73-2.93 N (30 days). In perforated packaging, the average weight change was 0.00-21.74 g (15 days), the average moisture content change was 86.50%-85.0% (30 days), the average color change L* was 54.35, a* 29.69, and b* 54.35 (30 days), and the average texture was 4.73-2.03 N (30 days). Based on the results of a comparative analysis of the four types of packaging, plastic wrapping proved to be the most effective in maintaining carrot quality during cold storage until signs of damage appeared. Keywords: Carrots, Vacuum Packaging, Non-Vacuum Packaging, Plastic Wrapping, Perforated Plastic.